The Quality of Red Bell Pepper Subjected to Freeze-Drying Preceded by Traditional and Novel Pretreatment - Katarzyna Rybak; Artur Wiktor; Dorota Witrowa-Rajchert; Oleksii Parniakov; Małgorzata Nowacka (Foods, 2021)
It has been demonstrated previously in the literature that utilization of PEF or a combination of a pulsed electric field (PEF) and ultrasounds (US) can facilitate dehydration processes and improve the quality of dried products even better than the application of thermal methods such as blanching. The aim of the study was to evaluate the quality of red bell pepper subjected to freeze-drying preceded by blanching or PEF or US treatment applied in a single and combined mode. Furthermore, the freeze-drying was preceded by shock freezing or vacuum freezing performed inside the freeze-dryer as a result of pressure drop during the first stage of freeze-drying. All of the analyzed technological variants enhanced the drying kinetics when compared to the intact material. Freeze-dried bell pepper subjected to non-thermal pretreatment exhibited higher vitamin C, total phenolic and carotenoids content than blanched material despite the fact that blanching reduced drying time the most compared to all other analyzed methods.